Leprosy Reaction in Thai Population: A 20-Year Retrospective Study - Poonkiat Suchonwanit; Siripich Triamchaisri; Sanchawan Wittayakornrerk; Ploysyne Rattanakaemakorn (Hindawi Limited, 2015)
Background. Leprosy is a chronic infectious disease that presents with varying dermatological and neurological symptoms. The leprosy reactions occur over the chronic course of the disease and lead to extensive disability and morbidity. Objective. To analyze and identify the risk factors which contribute to leprosy reactions. Methods. In a retrospective study, we reviewed the medical records of leprosy patients registered at the leprosy clinic, Ramathibodi Hospital, Thailand, between March 1995 and April 2015. One hundred and eight patients were included; descriptive analysis was used for baseline characteristics and a binary logistic regression model was applied for identifying risk factors correlated with leprosy reactions. Results. Of the 108 cases analyzed, 51 were male and 57 were female. The mean age of presentation was 45 years. The borderline tuberculoid type was the most common clinical form. Leprosy reactions were documented in 61 cases (56.5%). The average time to reaction was 8.9 months. From multivariate analysis, risk factors for leprosy reactions were being female, positive bacillary index status, and MB treatment regimen. Conclusions. Leprosy reactions are common complications in leprosy patients. Being female, positive bacillary index status, and multibacillary treatment regimen are significantly associated with the reactions. Early detection in cases with risk factors followed by appropriate treatment could prevent the morbidity of leprosy patients.